Efektivitas Berbagai Jenis ZPT Alami Terhadap Perkecambahan dan Pertumbuhan Bibit Markisa Ungu (Passiflora edulis) - Dwi Prasetyawati Thana (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Kristen Indonesia Toraja, 2017)
This study aims to (i) to determine the effect of each type of natural ZPT on germination and growth of passionfruit seedlings and (ii) to know the type of ZPT which has good effect on germination and growth of passionfruit seedlings. This study used Completely Randomized Design (RAL) with 6 different treatment levels repeated 3 times, so there are 18 units of treatment. Each treatment unit on germination there are 20 medium seeds in the nursery. There are 4 units of plants. The following is the treatment of natural ZPT that was tested that is (1) Z0 = control / without treatment, (2) Za = banana gong, (3) Zb = bamboo shoots, (4) Zc = Snails, (5) Zd = cow urine, and (6) Ze = young coconut water. The results showed that (i) giving natural ZPT had an effect on germination and growth of Purple Passion seeds and (ii) giving ZPT of young coconut water (Ze) has the best effect on observed growth component such as: seed viability, seed height, leaf number and volume the root of passion fruit seedlings.